Shaping industrial spatial density: How floor area ratio varies across regions and sectors in Zhejiang, China - Fan Tu; Ruijia Ji; Jinyu Zhou; Gabriel Hoh Teck Ling (PLoS ONE, 2026)
Spatial density plays a pivotal role in influencing land-use patterns and land consumption. To meet evolving industrial needs and maximize limited land resources, incorporating floor area ratio (FAR) optimization into urban planning is essential. Existing studies on floor area ratio largely focus on residential land, overlooking how industrial FAR varies across regions and sectors and what drives these differences. This study addresses this gap by analyzing newly supplied industrial land data from 90 counties in Zhejiang Province, China (2019–2023), using panel regression analysis. The findings reveal a steady FAR increase of 6.8% annually, with the highest levels in the northern coastal cities Hangzhou and Ningbo, a mid-range peak around Jinhua, and relatively lower but rising values toward the southern areas including Wenzhou. FAR is positively associated with land prices and government land supply, but negatively with per capita arable land. Significant regional and industrial disparities are observed, shaped by geography, land price and industry structure. These findings underscore the need for adaptive FAR policies that balance land efficiency and industrial compatibility. The study recommends stabilizing industrial land prices, supporting clustered small and micro enterprises with higher-density development, and selectively implementing the Industry’s Going Upstairs (IGU) strategy based on structural load, production characteristics, and suitability for mixed-use.